KETERGANTUNGAN GADGET DAN DAMPAK PADA PERKEMBANGAN ANAK - Atma Lutfia Rizki; El-Syifa Qolbi, Hidayati, Nayla Widi Fatiha, Pika, Putri Nanda,Tri Nopriza, Sriliza (CV. ADIBA AISHA AMIRA, 2026)
This study aims to identify the impacts of gadget use on early childhood and elementary school children. In the current digital era, gadgets play an important role in learning activities and access to information. However, improper and excessive use of gadgets may lead to dependency among children. The phenomenon observed today clearly indicates that many children experience gadget addiction, which can hinder the learning process. The research method employed in this study is a literature study, conducted by collecting and analyzing data from scientific journals, books, and relevant previous studies related to the research topic. The results show that many early childhood children experience gadget dependency, which affects various aspects of development, including social, emotional, cognitive, and physical development, as well as behavioral changes. Social impacts include a decline in children’s interaction and communication skills with their surrounding environment. Excessive gadget use can also reduce children’s concentration and thinking abilities. Therefore, parental supervision and education regarding appropriate gadget use for elementary school children are essential, along with limiting gadget usage to support optimal child development.